Fostering Tolerance: The Effectiveness of The Religious Education Policy Model in Religion-Based Higher Education in Creating a Culture of Religious Tolerance - Saerozi, Muh; Erlangga, Rifqi Aulia; bt Abdul Hamid, Nor Adha (Millati: Journal of Islamic Studies and Humanities, 2023)
The aim of this research is to examine the religious education policies of private universities in Indonesia that have a minority-religion base in a majority-religion environment. The three universities selected as samples were Universitas Pendidikan Muhammadiyah (Unimuda) Sorong, Universitas Santu Paulus (Unika) Ruteng, and Universitas Kristen Satya Wacana (UKSW) Salatiga. According to the qualitative study, UNIMUDA Sorong is the only university that has adopted confessional pluralism. Confessional pluralism found to be the best model for religious education. Unimuda’s confessional religious education model provides religious education courses tailored to each student’s religion. Meanwhile, two other colleges, Unika Ruteng and UKSW Salatiga, are implementing a semi-confessional pluralism policy. This semi-confessional pluralism policy is the novelty of this study. This policy establishes religious education as a general subject with general content that covers the six formal religions in Indonesia.